Chemical-Based Rodent Control Programs as a Zoonosis Control Measure: Proposal of Guidelines for Empirical Proof Studies - Caio Graco Zeppelini (Zoonotic Diseases)
Rodent-borne diseases threaten global public health, impacting the urban poor. Despite widespread application of rodenticide in rodent/rodent-borne disease control programs, empirical evidence demonstrating their effectiveness is lacking. This review proposed guidelines for designing and implementing empirical studies on rodenticides as public health measures. The recommendations include: (i) the importance of the type of quasi-experimental design adopted, and how it creates robust evidence; (ii) how urban slums present both challenges for control and ideal settings for studies; (iii) partnering with pest control authorities and community engagement for long-term viability; (iv) leveraging zoonotic systems with direct/environmental transmission, reliable diagnosis, and high prevalence for effectivity assessment; (v) pairing human cohort studies to observe epidemiological links; (vi) systematic data collection and management protocols; (vii) short- and long-term goals for critical evaluation and course-correction; (viii) focus on mechanistic approach; (ix) the need for standardized reporting of the findings.